Kajian Yuridis Tentang Pelaksanaan Poligami Beserta Akibat Hukumnya Perspektif Hukum Islam dan Undang-Undang : (Studi Kasus Di Pengadilan Agama Bondowoso Nomor Perkara 1580/Pdt.G/2021/PA.Bdw) - Firatul Kamila; Bachrul Ulum; Zaenol Hasan (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This thesis discusses: 1) Juridical Review of Polygamy Case study Case number 1580/Pdt.G/2021/PA.Bdw at the Bondowoso Religious Court. 2) Juridical Review of Polygamy according to Islamic Law at the Bondowoso Religious Court. 3) Juridical Review of Polygamy according to Islamic Law and the Law on Case Studies case number 1580/Pdt.G/2021/PA.Bdw at the Bondowoso Religious Court. The purpose of this study is to find out the review of Islamic law and the law regarding the practice of polygamy, considering the decisions taken in the case of the Bondowoso Religious Court. This type of research is field research, namely a research conducted in the field or at a research location, or a place chosen as a location to investigate objective phenomena. This research is carried out intensively, in detail and in depth on a particular object by studying it as a case. The results of this study are that the concept of polygamy according to Islamic law is a reference for husbands who want to carry out polygamy. The concept of justice in polygamy according to Islamic law at the Bondowoso Religious Court is in accordance with what has been exemplified by Rasulullah SAW, because it follows all the requirements and procedures that have been stipulated in Law no. 1 of 1974 concerning Marriage and the Compilation of Islamic Law itself. For further researchers, Suggestions that can be given related to this research are expected for future researchers to add more sources to find reports on polygamy in the Religious Courts and the object of this research is expected to be expanded.